Interrogating Datafication 2022
DOI: 10.1515/9783839455616-006
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Curation? Attending to Data, Records and Record Keeping in the Practices of Self-Monitoring

Abstract: This paper is concerned with everyday data practices, considering how people record data produced through self-monitoring. The analysis unpacks the relationships between taking a measure, and making and reviewing records. The paper is based on an interview study with people who monitor their blood pressure and/or body mass index/weight. Animated by discussions of 'data power' which are, in part, predicated on the flow and aggregation of data, we aim to extend important work concerning the everyday constitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Here, I build on the work of scholars underscoring the sensory and affective dimension of self‐tracking (Lupton, 2018; Maslen, 2021; Ruckenstein, 2014; Weiner et al., 2020). By detailing how users relate and negotiate different types of data in reproductive self‐tracking, my analysis taps into a new field to explore sensory knowing.…”
Section: Introductionmentioning
confidence: 99%
“…Here, I build on the work of scholars underscoring the sensory and affective dimension of self‐tracking (Lupton, 2018; Maslen, 2021; Ruckenstein, 2014; Weiner et al., 2020). By detailing how users relate and negotiate different types of data in reproductive self‐tracking, my analysis taps into a new field to explore sensory knowing.…”
Section: Introductionmentioning
confidence: 99%
“…clinicians (Nielsen, 2015;Piras and Miele, 2017;Danesi et al, 2018;Weiner et al, 2020) to either facilitate or avoid particular conversations. This curatorial work is often invisible to clinicians and provides another avenue for patients to pursue their own concerns without directly challenging the authority of their clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…This paper draws on data collected as part of a 3-year study of self-monitoring, focussing on the cases of blood pressure (BP) and weight/BMI, with this paper focusing solely on BP monitoring. Ethical approval was given by the lead author's institutional Ethics Review Committee and full details of the overall study design and methods can be found in Weiner et al (2020), and Andrews et al (2020). Two distinct data sets are drawn on in this paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations